Meningkatkan Hasil Belajar Matematika Pada Kompetensi Memahami Bentuk Akar Serta Penggunaannya Dalam Pemecahan Masalah Sederhana Melalui Penerapan Model Pembelajaran Kooperatif Siswa Kelas IX A SMP Negeri 2 Sangalla Tana Toraja (LPPM UKI Toraja, 2019)
The aimed of this study was to examine student activities in cooperative learning. The study was conducted in Mathematics Subjects in SMP Negeri 2 Sangalla Tana Toraja Second Semester of Learning Year 2016/2017. The population (Subject) studied were students of class IXA of SMP Negeri 2 Sangalla Tana Toraja. Data collection methods use the results of the final test of each cycle to determine the efficacy of student learning, the results of observations and the results of the questionnaire given to students to determine student responses to the application of cooperative learning models. Collect data were using Questionnaire, authentic assessment to get the progress of learning material (level of achievement) mathematics, observation, interview and document study. The results of this study consisted of 3 cycles, namely cycle 1, cycle 2 and cycle 3. Cycle 1 shows the average cognitive learning outcomes of 67 and completeness of 68%, the average affective learning outcomes of 65.62 and 75% completeness and the average psychomotor learning outcomes of 73.43 and 93.75% completeness. Cycle 2 shows the average cognitive learning outcomes of 70 and completeness of 87,5%, the average affective learning outcomes of 70,31 and 87,5% completeness and the average psychomotor learning outcomes of 85,93 and 93.75% completeness. Cycle 3 shows the average cognitive learning outcomes of 73 and completeness of 100%, the average affective learning outcomes of 71,81 and 100% completeness and the average psychomotor learning outcomes of 87,50 and 100% completeness. Based on the results of data analysis, it can be concluded that the application of the Cooperative Learning Model Can Improve Mathematics Learning Outcomes in Competence to understand the root form and its use in simple problem solving. The application of cooperative learning models in mathematics learning can increase enthusiasm in teaching and learning activities.